MASCULINITY IN QUESTION IN TIME OF UNEMPLOYMENT IN WENDY HOLDEN’S THE FULL MONTY - M. Djundjung, Jenny; Irawan, Stefanny (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Men see masculinity as a form of identity as an individual as well as a group. This identity is usually attached to the jobs men have because of the traditional gender work division where men is put in a role as a breadwinner of their families. When they are out of work, they also lose their sense of identity, hence, their sense of worth as they think that they are on the brink of losing their masculinity. This is the condition that befalls the three male characters, Gaz, Dave and Gerald, in The Full Monty. They feel that they have lost their masculinity when they lose their works thus, they hold on to ways that they think can preserve their sense of worth.